Model–data synthesis for the next generation of forest free‐air CO2 enrichment (FACE) experiments. Issue 1 (6th August 2015) - Norby, Richard J.; De Kauwe, Martin G.; Domingues, Tomas F.; Duursma, Remko A.; Ellsworth, David S.; Goll, Daniel S.; Lapola, David M.; Luus, Kristina A.; MacKenzie, A. Rob; Medlyn, Belinda E.; Pavlick, Ryan; Rammig, Anja; et al.
Summary: The first generation of forest free‐air CO2 enrichment (FACE) experiments has successfully provided deeper understanding about how forests respond to an increasing CO2 concentration in the atmosphere. Located in aggrading stands in the temperate zone, they have provided a strong foundation for testing critical assumptions in terrestrial biosphere models that are being used to project future interactions between forest productivity and the atmosphere, despite the limited inference space of these experiments with regards to the range of global ecosystems. Now, a new generation of FACE experiments in mature forests in different biomes and over a wide range of climate space and biodiversity will significantly expand the inference space. These new experiments are: EucFACE in a mature Eucalyptus stand on highly weathered soil in subtropical Australia; AmazonFACE in a highly diverse, primary rainforest in Brazil; BIFoR‐FACE in a 150‐yr‐old deciduous woodland stand in central England; and SwedFACE proposed in a hemiboreal, Pinus sylvestris stand in Sweden. We now have a unique opportunity to initiate a model–data interaction as an integral part of experimental design and to address a set of cross‐site science questions on topics including responses of mature forests; interactions with temperature, water stress, and phosphorus limitation; and the influence of biodiversity.